k3=11

Simple and best practice solution for k3=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for k3=11 equation:



k3=11
We move all terms to the left:
k3-(11)=0
We add all the numbers together, and all the variables
k^3-11=0
We do not support ekpression: k^3

See similar equations:

| 8x*5=80 | | 3.8-2.5x=5 | | -12=-(x+3)+4 | | 8y+7=2(4y+3) | | 8+9c=6+10c-4c | | (2x+7)(x)=30 | | 2y+33y=5 | | (m/3)–4=–1 | | .75(-8)+b=-18 | | (x/6)+10=14 | | 6(t-3)=2(9-21) | | -6c+24=-3c–3c+17 | | 6x-9=-15+4x | | 9d-2d+6d+2=6d | | 60=6(v+7) | | -1/2x-8/7=-1/3 | | 10(h+1)-4=74 | | 2.6=7.1-0.9x | | -5/3=1/5w-3/2 | | 10=3(v-5) | | -2w−2=-w−10 | | 10j=-10+9j | | 45+4×x=61+2x | | 10−6m=-9−3m−5 | | (18-2x)(11-2x)=1 | | 8z-7=3z-8 | | 82-22=3(3z+11)-z | | n-8-3n=6 | | -6x+42=15x | | 7x+-8=5x+2 | | -1−5f=-4f−10 | | 6r+10=8r |

Equations solver categories